Optical genome mapping identifies a homozygous deletion in the non-coding region of the SCN9A gene in individuals from the same family with congenital insensitivity to pain - Boughalem, Aïcha; Ciorna-Monferrato, Viorica; Sloboda, Natacha; Guegan, Amélie; Page, François; Zimmer, Sophie; Benazra, Marion; Kleinfinger, Pascale; Lohmann, Laurence; Valduga, Mylène; Receveur, Aline; Martin, Fernando; et al. (Frontiers in Genetics, 2024)
We report an index patient with complete insensitivity to pain and a history of painless fractures, joint hypermobility, and behavioral problems. The index patient descends from a family with notable cases among his maternal relatives, including his aunt and his mother’s first cousin, both of whom suffer from congenital insensitivity to pain. The patient had normal results for prior genetic testing: fragile-X syndrome testing, chromosomal microarray analysis, and exome sequencing. Optical genome mapping detected a homozygous deletion affecting the noncoding 5′ untranslated region (UTR) and the first non-coding exon of the SCN9A gene in all affected family members, compatible with recessive disease transmission. Pathogenic homozygous loss-of-function variants in the SCN9A gene are associated with impaired pain sensation in humans. Optical genome mapping can thus detect pathogenic structural variants in patients without molecular etiology by standard diagnostic procedures and is a more accessible diagnostic tool than short-read or long-read whole-genome sequencing.